Urban Multiculturalism and SDG 11: The Role of Little India in Promoting Inclusive City Development in Medan - Siti Fajrina; Rachmaniar Rachmat Nur Wisisono; Stivani Ismawira Sinambela; Ilovia Aya Regita Widayat; Ibnu Zulian; Tia Ifada (UNIDA Gontor, 2026)
The achievement of the Sustainable Development Goals (SDGs) at the local level is a key factor in supporting inclusive and sustainable urban development. One example of this can be seen in the Little India or Kampung Madras area of Medan, which embodies cultural diversity and the enduring identity of the Tamil Indian community. This study aims to examine the characteristics of Little India as a multicultural space, analyze its contribution to achieving SDG 11, and identify opportunities and challenges for its development as an ethically inclusive area. The research employs a qualitative method, drawing on a literature review and documentary analysis of policy documents, government publications, and various academic references. The analysis combined the concepts of Urban Multiculturalism and Localizing the SDGs. The results of the study indicate that Little India functions as a space for cross-cultural interaction that supports the preservation of Tamil Indian cultural heritage whilst strengthening Medan's identity as a multicultural city. This area contributes to achieving SDG 11 by strengthening social inclusion, preserving cultural heritage, and providing public spaces accessible to diverse community groups. In addition to its social and cultural value, Little India can also support the local economy through trade, culinary activities, and cultural tourism. These findings indicate that preserving local culture can play a vital role in achieving inclusive and sustainable urban development.